Dental Health Status in Asthmatic Children - M - Ghasempour; I Mohammadzade; K. Hosaininia; K. Hosaininia (Isfahan University of Medical Sciences, 2006)
Introduction: Asthma is a common disorder that affects children. Only a limited number of studies have investigated the effect of asthma on dental caries. The purpose of this study was to determine the dental caries status in children with bronchial asthma.Methods and Materials: In this crossectional study, 75 asthmatic and 75 non asthmatic children who were matched according to age and sex were examined for dental caries. All children were four to Eighteen years old. The children were divided into four groups according to the severity of bronchial asthma as mild, moderate, Severe and intermittant asthma. They were also distributed according to the dental status as primary and permanent dentition and depending on the medication being used into inhaler, syrup, tablet and combination group. The data were analysed with Mann-Wintney and Kruscall-Wallis tests.Results: A significant difference was found in DMFT between asthmatic group (2.27±2.65) and control group (0.8±1.41) but significant difference was found in DMFT between asthmatic (3.53±3.06) and control group (3.22±3.13). Mean of DMFT in asthmatic male was significantly more than the control group and also there was a significant difference in DMFT in children between 11-18 years old. There was no significant difference between asthmatic and control groups regarding severity of the disease, kind of drugs and the method the medication used.Conclusion: It was concluded that asthmatic children had higher caries prevalence in their permanent teeth, and the severity and the method of the mediaction being used had no effect on the dental caries in asthmatic children.Key words: Asthma, Decay, DMFT, dmft.